Preoperative hemoglobin and perioperative blood transfusion in major head and neck surgery: a systematic review and meta-analysis - Munib Ali; Joseph C. Dort; Khara M. Sauro (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background There is a growing concern with inappropriate, excessive perioperative blood transfusions. Understanding the influence of low preoperative hemoglobin (Hgb) on perioperative blood transfusion (PBT) in head and neck cancer (HNC) surgery with free flap reconstruction may help guide clinical practice to reduce inappropriate treatment among these patients. The objective is to synthesize evidence regarding the association between preoperative Hgb and PBT among major HNC free flap surgeries. Methods Terms and synonyms for HNC surgical procedures, Hgb and PBT were used to search MEDLINE, Embase, CINAHL, Cochrane Central Register of Controlled Trials and Cochrane Database of Reviews from inception to February 2020. Reference lists of included full texts and studies reporting the preoperative Hgb, anemia or hematocrit (exposure) and the PBT (outcome) in major HNC surgery with free flap reconstruction were eligible. Studies examining esophageal, thyroid and parathyroid neoplasms were excluded; as were case reports, case series (n < 20), editorials, reviews, perspectives, viewpoints and responses. Two independent, blinded reviewers screened titles, abstracts and full texts in duplicate. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses was followed. A random-effects model was used to pool reported data. The primary outcome was the proportion of patients who had a PBT. Subgroup analysis examined sources of heterogeneity for perioperative predictors of PBT (age, sex, flap type, flap site and preoperative Hgb). We also examined mean preoperative Hgb in the PBT and no PBT groups. Results Patients with low preoperative Hgb were transfused more than those with normal Hgb (47.62%, 95% CI = 41.19–54.06, I2 = 0.00% and 13.92%, 95% CI = 10.19–17.65, I2 = 20.69%, respectively). None of the predictor variables explained PBT. The overall pooled mean preoperative Hgb was 12.96 g/dL (95% CI = 11.33–14.59, I2 = 0.00%) and was 13.58 g/dL (95% CI = 11.95–15.21, I2 = 0.00%) in the no PBT group and 12.05 g/dL (95% CI = 10.01 to 14.09, I2 = 0.00%) in the PBT group. Conclusions The heterogeneity between studies, especially around the trigger for PBT, highlights the need for additional research to guide clinical practice of preoperative Hgb related to PBT to enhance patient outcomes and improve healthcare stewardship. Graphical abstract